TERRITORIAL AND GEOGRAPHICAL LOCATION OF THE CITIES OF THE TERMIZ OASIS IN THE EARLY MIDDLE AGES - Hasanov Akram Muminovich (Journals Park Publishing, 2022)
This article through written sources and archeological research analyzes changes in urban planning traditions in the Termez oasis with the spread of Islam in region, how these changes led to the conversion of large castles and villages into cities in the early Middle Ages, to the abandonment of dual system in the structure of cities, that is, the construction of new arches while preserving the arches and shahristans, and the geographical location of large and small cities in the Termez oasis, such as Chaganiyon, Sarmingon, Charmingon, Hashimgird, Navandak, Vashgird, Barangi, Budrach, Darzangi.
Keywords: Shaharmonand, Chaghaniyon, Budrach